2020
DOI: 10.1177/2516608520976275
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Therapy and Direct Thrombectomy for Acute Ischemic Stroke: A Prospective Cohort Study

Abstract: Background: It remains controversial if intravenous thrombolysis (IVT) prior to mechanical thrombectomy (MTE) is superior to MTE alone in patients with acute ischemic stroke caused by large vessel occlusion. We aim to compare functional outcomes, mortality, reperfusion, and intracranial hemorrhage rates in bridging therapy (IVT prior thrombectomy) and MTE alone groups within 6 h from symptom onset. Materials and Methods: Consecutive hospitalized patients (September 2017 and July 2018) with acute large artery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Similar high recanalization rates were observed in the Korean ENCHANTED study on a subset of patients receiving alteplase bridging with MTE (low-dose IVT: 85% vs. standard-dose IVT: 76%) (18) and the Taiwanese study (low-dose IVT: 100% vs. standard-dose IVT: 69%) (19). In a study conducted in Southern Vietnam, among those with standard-dose alteplase bridging therapy, the recanalization rate was approximately 88% (onset to groin time ∼270 min) (21). Our study findings showed no significant time delays occurred between drip and groin puncture time (∼40 min; onset to groin time: up to 206 min), which may contribute to the high recanalization rates in both arms, despite a relatively high rate of large artery disease etiology presented in the study (∼50%).…”
Section: Discussionmentioning
confidence: 97%
“…Similar high recanalization rates were observed in the Korean ENCHANTED study on a subset of patients receiving alteplase bridging with MTE (low-dose IVT: 85% vs. standard-dose IVT: 76%) (18) and the Taiwanese study (low-dose IVT: 100% vs. standard-dose IVT: 69%) (19). In a study conducted in Southern Vietnam, among those with standard-dose alteplase bridging therapy, the recanalization rate was approximately 88% (onset to groin time ∼270 min) (21). Our study findings showed no significant time delays occurred between drip and groin puncture time (∼40 min; onset to groin time: up to 206 min), which may contribute to the high recanalization rates in both arms, despite a relatively high rate of large artery disease etiology presented in the study (∼50%).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, future prospective studies with larger sample size are recommended to establish the appropriate (Continued) threshold value of perfusion or ASPECTS-based imaging for EVT in patients presenting beyond 24 h. In Vietnam, the incidence of stroke occurs at a younger age (Table 1) compared to other developing countries. 2,3,18,19 Furthermore, younger stroke patients are associated with better outcomes and fewer complications following EVT compared to older patients. 20 This is particularly important given that young stroke patients have a longer life expectancy, and EVT may have a significant impact on their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In Vietnam, the incidence of stroke occurs at a younger age (Table 1) compared to other developing countries. 2,3,18,19 Furthermore, younger stroke patients are associated with better outcomes and fewer complications following EVT compared to older patients. 20 This is particularly important given that young stroke patients have a longer life expectancy, and EVT may have a significant impact on their quality of life.…”
Section: Discussionmentioning
confidence: 99%